Influência do ultrassom sobre a filtração aplicada ao tratamento de água produzida - Licona, Karla Patricia Macedo (2011)
Several Techniques have been studied for the treatment of produced water wastewater generated in the production of oil, in order to condition it for re-injection in oil-bearing formation, looking for the increase of production in the area or for reuse or proper final disposal. For these pruporses there are several treatment processes, including filtration, wich usually create a layer of solid particles in the medium porous of filter element. Filter rate declines gradually trhought the process. The objective of this work was to study the ultrasound influence on filtration using sintered plastic filter, regenerated to remove undesirable particulates material, and resistent from a mechanical and chemical standpoint, applied to the treatment of produced water in order to increase filtration capacity and decrease the time for its operation, with filter medium in a total area of the 3,5 x10-³ m² and properly tested in experiments with synthetic produced water and natural produced water obtained from the producing field of Carmópolis Sergipe Brazil. The results showed that use of the filtration system is viable for the treatment of produced water, in order to fit in re-injection standarts in oil reservoirs, since the removal efficiencies of total suspended solids (TSS) and oil and grease (TOG) were high, reaching values around 90%. It was concluded that techniques under conventional and ultrasound filtration, as well as strategies for filter media cleaning studied were very promising and should be better studied with the aim of developing a future technology on an industrial scale.